PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, DAN NILAI PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Luh Putu Alit Sukma Yuni; I Made Wianto putra; I Nyoman Sutapa (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2024)
This study discusses how to test and analyze the influence of liquidity, leverage, profitability and market value on stock returns in mining companies listed on the IDX for the 2023 period. The total sample in this study is 45 industries for the 2023 observation period, which was determined using purposive sampling techniques . This research uses quantitative data. The data used is secondary data in the form of company financial reports on the IDX from the website www.idx.co.id. The data collection method in this research uses documentation study techniques. The data analysis technique used is multiple linear regression analysis technique using the SPSS program as an analysis tool.